Understanding Cloud-Native Architectures for Scalable Systems: A Comprehensive Analysis - Pakalapati, Maruti Pradeep (International Journal of Computing and Engineering, 2025)
Cloud-native architectures have fundamentally changed how engineers build scalable, resilient distributed systems. This article tracks the gradual evolution away from monolithic applications toward more flexible microservices-based designs. Four essential principles emerge as defining characteristics: decomposition of services, container-based deployment, automated orchestration, and standardized API communication. Technical implementation details receive thorough attention, from the practical challenges of container runtime selection to the nuanced configuration of orchestration platforms and service mesh deployments. The article deliberately examines critical design decisions facing architects: choosing appropriate scaling mechanisms, managing stateless operations, implementing fault-tolerant behaviors, and developing sophisticated traffic routing. Operational concerns—particularly monitoring capabilities, security controls, and deployment pipelines—reveal themselves as equally important to technical architecture. Numerous organizations have documented significant improvements in operational metrics, infrastructure costs, and service stability after adopting these architectural patterns. The tensions between theoretical benefits and implementation complexities remain evident throughout, reflecting the genuine trade-offs architects must navigate when establishing cloud-native systems across diverse business environments and technical constraints.